Neutrinos and Implications for Physics Beyond the Standard Model: Stony Brook 11 - 13 October 2002 - Shorock R. (World Scientific, 2003)
This volume presents the proceedings of the conference "Neutrinos and Implications for Physics Beyond the Standard Model", put on by the Yang Institute for Theoretical Physics, State University of New York at Stony Brook. The observation of neutrino masses and lepton mixing constitutes the first confirmed evidence for physics beyond the Standard Model. This evidence includes the measured deficiency of charged current reactions induced by solar neutrinos and the anomalous zenith angle distribution of atmospheric neutrinos. A profound question now facing theorists is: What do these observations imply for new physics? At the conference, members of the major experiments gave an update on current experimental evidence from solar and atmospheric neutrino data for neutrino oscillations, and status reports from KamLAND and MiniBooNE. Leading theorists also reported on neutrinoless double beta decay, high energy neutrino scattering and precision electroweak data, theoretical models for neutrino masses and lepton mixing, and constraints from neutrino data. Since neutrino physics is at present one of the most exciting areas of particle physics, this volume should be of interest to a wide variety of students and researchers in physics.